Odd‐Even Effects on Transport Properties of Polycyclic Arene Molecular Devices with Decreasing Numbers of Benzene Rings. Issue 6 (18th February 2020) - Xia, Yujie; Li, Tao; Yuan, Chao; Fletcher, Cameron; Dai, Xinyue; Zhang, Xingfan; Zhang, Lishu; Jiang, Yanyan; Li, Hui
Abstract: The electron transport properties of polycyclic aromatic hydrocarbons (PAHs) with different numbers of benzene rings tethered to narrow zigzag graphene nanoribbon (ZGNR) electrodes have been investigated. Results show that the transport properties of PAHs are dependent on whether the number of benzene rings in the width direction is odd or even. This effect is strong for narrow width PAHs, but its strength decreases as the width of the PAH is increased. PAHs with an odd number of rings exhibit poor transport properties, whereas the ones having an even number of rings show excellent transport properties coupled with a negative differential resistance (NDR) effect. Moreover, the linkage points and the structure of the molecules have a noticeable effect on the transport properties of the PAH, making the odd‐even effect weaker or disappear entirely. Although the PAH with three benzene rings displays poor transport capabilities, it shows excellent rectification behavior compared to the other examined molecules. These studies present a feasible avenue for designing molecular devices with enhanced performance by the careful manipulation of the PAH molecular structure. Abstract : That′s odd : Polycyclic arene molecules with varying numbers of benzene rings clearly display an interesting odd‐even effect on their electron transport properties.